2019
DOI: 10.1021/jacs.9b11178
|View full text |Cite
|
Sign up to set email alerts
|

A Catalytic Approach for Enantioselective Synthesis of Homoallylic Alcohols Bearing a Z-Alkenyl Chloride or Trifluoromethyl Group. A Concise and Protecting Group-Free Synthesis of Mycothiazole

Abstract: A protecting group-free strategy is presented for diastereo-and enantioselective routes that can be used to prepare a wide variety of Z-homoallylic alcohols with significantly higher efficiency than is otherwise feasible. The approach entails the merger of several catalytic processes and is expected to facilitate the preparation of a wide range of bioactive organic molecules. More specifically, Z-Chloro-substituted allylic pinacolatoboronate is first obtained through stereoretentive cross-metathesis between Z-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 79 publications
0
20
0
Order By: Relevance
“…The above findings insinuated that it might be possible to exploit steric factors to improve e.r. We recently showed that additions of Z ‐disubstituted allyl boronates to ketones or aldehydes are more enantioselective probably because the substituent at the stereogenic carbon center of the chiral allyl boronate (e.g., Me unit in VI , Scheme a) prefers to be oriented pseudo‐axially, away from the catalyst framework . Accordingly, we investigated the reaction with Z ‐crotyl–B(pin) (( Z )‐ 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The above findings insinuated that it might be possible to exploit steric factors to improve e.r. We recently showed that additions of Z ‐disubstituted allyl boronates to ketones or aldehydes are more enantioselective probably because the substituent at the stereogenic carbon center of the chiral allyl boronate (e.g., Me unit in VI , Scheme a) prefers to be oriented pseudo‐axially, away from the catalyst framework . Accordingly, we investigated the reaction with Z ‐crotyl–B(pin) (( Z )‐ 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…We opted for aminophenol‐based boryl systems to serve as catalysts. These are easy to prepare and modifiable entities that at the time had been used for enantioselective additions to aldimines, ketones, and aldehydes, but not the far less reactive NH‐ketimines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hoveyda, Romiti, and co‐workers developed the protecting group free and concise total synthesis of mycothiazole 1033 (Scheme 160). [342] In this vital synthetic approach, stereoretentive CM was one of the key steps utilized to forge the compound 1032 with Z ‐selectivity. Negishi‐type coupling between vinyl chloride 1028 and boronate 1029 in presence of Pd‐catalyst facilitated the triene derivative 1030 , which was then subjected to stereoretentive cross CM with Z ‐alkene 1031 in presence of Grubbs catalyst 7 to deliver a primary alcohol 1032 in 77% yield with >98% Z ‐selectivity.…”
Section: Various Strategies/tactics In Olefin Metathesis Reactionsmentioning
confidence: 99%
“…Due to the utility of allylic boron reagents in organic synthesis, chemists are increasingly attentive to their preparations. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Usually, basic main-group organometallics, such as organolithium or Grignard reagent, are necessary for traditional methods to make allylboranes. [19][20][21][22][23][24][25] The disadvantage of these strategies is their incompatibility with electrophilic functional groups.…”
Section: Introductionmentioning
confidence: 99%